Feeding the planet and the role of the Common Agricultural Policy (CAP) - Veerman, C.P. (Applied Studies in Agribusiness and Commerce, 2012)
Keynote speech held at the Second AGRIMBA-AVA Congress 2011 on Dynamics of International Cooperation in Rural Development and Agribusiness, 23-24 June, 2011, atWageningen, the Netherlands.